(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The quantitative composition of eight heavy metals in the soil, plants and fruits of tomato, cucumber and garlic was studied. The object of the study was the soil on which tomatoes, cucumbers, garlic and other crops were grown in the cities of Shekaftar. Five heavy metals were determined in soil and crop samples: Pb, Cu, Zn, Cr, Cd. According to the data obtained, a high content of lead, copper and cadmium was revealed in the studied soil. At the same time, the concentration of these metals was exceeded in tomato, cucumber and garlic plants. Thus, the greatest contribution to the contamination of tomato, cucumber and garlic plants comes from concentrations of zinc and lead of 12.4 and 8 mg/kg, respectively. The concentration of copper and chromium was 1.3 and 0.3 mg/kg, respectively, cadmium - 0.56. The concentration of lead is also higher in these plants - 0.6 mg/kg at 0.5, cadmium - 8 times higher than 0.03 mg/kg at 0.26 mg/kg. The analyzes also showed that the concentration of zinc was exceeded by 7 times, the concentration of copper by 6 times. We also calculated bioaccumulation (biological accumulation coefficient) as the ratio of the average content of heavy metals on tomato plants and fruits to their average content in soils. According to the